A framework to organize public transport-based crowdshipping - Meijing Zhang; Lynette Cheah (Journal of Public Transportation)
Crowdshipping is an urban freight solution that involves members of the public to fulfill parcel deliveries, ideally along their precommitted journeys. This paper proposes a comprehensive framework to organize public transport-based crowdshipping by integrating the use of parcel lockers. This approach allows transit passengers to serve as crowdshippers, ensuring that parcel delivery demand aligns with crowdshipper availability, while considering locker capacity constraints. The framework involves formulating and solving parcel assignment and vehicle routing problems, incorporating matching for parcels and lockers, and using an iterative heuristic algorithm for optimal locker selection. The feasibility of the framework is demonstrated using real-world data, revealing significant benefits. With crowdshipping, a carrier can reduce delivery vehicle kilometers traveled (VKT) and associated air emissions by up to 30%. This reduction only requires redirecting less than 9% of parcels to crowdshippers. Crowdshipping utilizing public transport has good potential to fulfill urban deliveries in a sustainable manner.